Trifluoromethylated hydrazones and acylhydrazones as potent nitrogen-containing fluorinated building blocks - Dongxu, Zhang (Beilstein Journal of Organic Chemistry, 2023)
Nitrogen-containing organofluorine derivatives, which are prepared using fluorinated building blocks, are among the most important active fragments in various pharmaceutical and agrochemical products. This review focuses on the reactivity, synthesis, and applications of fluoromethylated hydrazones and acylhydrazones. It summarizes recent methodologies that have been used for the synthesis of various nitrogen-containing organofluorine compounds.
Keywords: acylhydrazones; difluoromethylation; dihydropyridazine; fluorinated building blocks; hydrazones; imidazolidines; pyrazoles; pyrazolidines; pyrazolines; trifluoromethylation